Patients' preoperative background causes gastric stasis after laparoscopy‐assisted pylorus‐preserving gastrectomy. Issue 4 (23rd March 2018) - Nishizawa, Nobuyuki; Hosoda, Kei; Moriya, Hiromitsu; Mieno, Hiroaki; Ema, Akira; Ushiku, Hideki; Ishii, Satoru; Tanaka, Toshimichi; Washio, Marie; Yokoi, Keigo; Harada, Hiroki; Watanabe, Masahiko; et al.
Abstract: Introduction: Despite technical improvements in laparoscopic gastrectomy, gastric stasis is still a serious problem in laparoscopy‐assisted pylorus‐preserving gastrectomy (LAPPG). The aim of this study was to investigate the factors that might cause gastric stasis in LAPPG. Methods: From April 2004 through November 2012, 85 patients with cT1N0 middle‐third gastric cancer who underwent LAPPG at Kitasato University Hospital; these patients were included in the present study. Infra‐pyloric vein (IPV)‐preserving LAPPG was performed in 41 patients. We compared the rate of gastric stasis in the IPV‐preserving and the IPV–non‐preserving groups, and analyzed the clinicopathological factors that might have caused gastric stasis. Results: We did not demonstrate that preservation of the IPV could prevent gastric stasis in the early and late postoperative periods. Symptoms of gastric stasis were most frequently recognized 1 year after surgery. A significantly higher proportion of preoperative ASA class 2 patients had gastric stasis than did not (80.0% [12/15] vs 48.6% [34/70], P =0.02). Among the ASA class 2 patients, a significantly greater proportion of those with depressed activities of daily living than those with normal activities of daily living had gastric stasis (66.7% [4/6] vs 20.0% [8/40], P = 0.015). Conclusions: The clinical significance of the IPV preservation in LAPPG could not be demonstrated. LAPPG should be performed for ASA class 1 patients or those with maintained preoperative activities of daily living.